Is Europe good for you? : EU spending and well-being / Lisa Dellmuth ; with a foreword by Bo Rothstein. - Dellmuth, Lisa, 1981- (Bristol shorts research., 2021)
This important book investigates how the European Union (EU) can use its regional funding programmes in ways that increase citizen well-being. It argues the case for enhancing the inclusivity of EU growth, which yields the promise of a more legitimate and stronger union.